Woklife balance: Efforts to Increase Organizational Commitment and Employee Performance - Ismaila - (Entrepreneurship Undergraduate Program at Amkop Business School, 2023)
Organizational commitment and employee performance are things that need to be considered in order to achieve the company's vision and mission. This study aims to determine the extent of the influence of worklife balance on organizational commitment and employee performance of Bank Sulselbar Bulukumba Main Branch. This research uses a quantitative approach that intends to explain the position of the variables studied and the relationship between one variable and another. Research on the effect of Work Life Balance and Organizational Commitment on Employee Performance at Bank Sulselbar Bulukumba Main Branch found empirical facts that worklife balance has a significant positive effect on organizational commitment and employee work but for indirect influence, organizational commitment has not been able to become a mediating variable to estimate the effect of worklife balance on employee performance.